Characteristics of School Injuries Presenting to the Emergency Department - Özdemir, Serdar; Akça, Hatice Şeyma; Algın, Abdullah; Kokulu, Kamil; Özkan, Abuzer (Avicenna Journal of Medicine, 2022)
Background School injuries account for approximately one-fifth of pediatric injuries. We aimed to investigate the frequency and severity of school injuries among school-aged children and determine clinical diagnoses and surgery requirement data.Methods In this prospective study, children who were admitted to the emergency department due to school accidents over a 5-month period were included. Demographics, activity during trauma, mechanism of trauma, nature, severity, emergency department outcomes, and surgery requirement were evaluated.Results The study included a total of 504 school-aged children, of whom 327 (64.9%) were male and 177 (35.1%) were female. Of the children, 426 (84.5%) had no evidence of injury or minor injury, while 78 (15.5%) had moderate or severe injury. There was a statistically significant difference between these two groups in terms of gender (p = 0.031). Of the 78 children with moderate or severe injuries, 45 had extremity fractures, 18 had lacerations, 5 had maxillofacial injuries, 4 had cerebral contusion, 1 had lung contusion, and 1 had cervical soft-tissue damage. Two patients with fractures and two with eyelid lacerations were treated surgically, and four patients with brain contusion were hospitalized for a close follow-up.Conclusion This study revealed that the most common moderate or severe injuries in school accidents referred to emergency department were distal radius fractures and lacerations.
Keywords: school health; school; child; injury; fracture; lacerations